An introduction to management science quantitative approaches to decision making - Anderson, David Ray (Cengage South-Western, 2010)
Introduction to Management Science, 9e blends problem formulation, managerial interpretation, and math techniques with an emphasis on problem solving. The problem-scenario approach introduces quantitative procedures through situations that include both problem formulation and technique application Extensive linear programming coverage includes problem formulation, computer solution, and practical application. Text covers transportation, assignment, and the integer programming extension of linear programming, as well as advanced topics like waiting line models, simulation, and decision analysis. Large selection of problems includes self-test problems with complete solutions and 20 case problems.